2018
DOI: 10.1186/s13063-018-2440-y
|View full text |Cite
|
Sign up to set email alerts
|

Global health trials methodological research agenda: results from a priority setting exercise

Abstract: BackgroundMethodological research into the design, conduct, analysis and reporting of trials is essential to optimise the process. UK specialists in the field have established a set of top priorities in aid of this research. These priorities, however, may not be reflected in the needs of similar research in low- to middle-income countries (LMICs) with different healthcare provision, resources and research infrastructure. The aim of the study was to identify the top priorities for methodological research in LMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 6 publications
0
30
0
Order By: Relevance
“…However, despite Polish and Brazilian Portuguese versions being distributed, via direct email to members of patient organizations, participation was low, with only one person completing R1 of the Delphi in Polish. Choosing appropriate outcomes to measure is a top methodological priority for trialists working in low-income and middle-income countries (LMICs) 42. A recent review found the number of COS being developed in some LMICs has increased,41 yet the number of participants in each COS, the methods of engagement and the source of recruitment have yet to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite Polish and Brazilian Portuguese versions being distributed, via direct email to members of patient organizations, participation was low, with only one person completing R1 of the Delphi in Polish. Choosing appropriate outcomes to measure is a top methodological priority for trialists working in low-income and middle-income countries (LMICs) 42. A recent review found the number of COS being developed in some LMICs has increased,41 yet the number of participants in each COS, the methods of engagement and the source of recruitment have yet to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…A survey has recently been undertaken to identify the top priorities for trials methodological research in LMICs to inform further research and ultimately to improve clinical trials in these regions. The priority most commonly graded as critically important, amongst 400 participants from over 80 countries, was choosing appropriate outcomes to measure [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The views expressed here relate to the present delivery of publicly funded trials in the UK and may suffer from limited external validity to other contexts where funding and CTU arrangements may differ. Note also that priorities for methodological research differ between settings, with recruitment and retention less of an issue in low- and middle-income countries compared to outcome assessments [ 13 ].…”
Section: Discussionmentioning
confidence: 99%